(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An elevator is one of the circulation systems in a building that is classified as a vertical circulation system in the building. Transportation planning in buildings must be in accordance with laws, ministerial regulations, regional regulations and standards, which become a reference in planning procedures. The xxx apartment building located in East Jakarta is an apartment building consisting of 2 towers (Tower A and B), each of which consists of a total of 25 floors (24 floors + 1 basement), 1 floor roof, each 87.3 meters high. , the number of occupants of building A is 727 people and building B is 748 people. Traffic analysis is needed to determine the type of lift suitable for the building. The method used in this research is to use the Indonesian National Standard, SNI 03-6573-2001. From the results of traffic analysis calculations for buildings A and B obtained, the selected elevator for apartment building A is an elevator with a capacity of 15 people (1000 kg) with a speed of 90 mpm, a total of 3 units. And apartment building B is an elevator with a capacity of 15 people (1000 kg) with a speed of 90 mpm, a total of 3 units.